Efektivitas Project Based Learning dalam Kurikulum Merdeka terhadap Kemampuan Berpikir Kritis Matematis Siswa SMP Negeri 1 Karangdadap - A’izah, Dewi Lailatul; Dewi, Heni Lilia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to analyze whether the application of the Project Based Learning model in the Independent Curriculum is effective on the mathematical critical thinking ability of SMP Negeri 1 Karangdadap students. This type of research is Equivalent Control Group Design. The data collection techniques are tests, observations, and documents. Meanwhile, the data analysis techniques used are early stage data analysis including normality test, homogeneity test and mean equation test, final stage data analysis includes normality test, homogeneity test, mean difference test (t-test), and N-Gain test. Based on the results of the assessment of teacher activities (researchers) got a score of 53 with a percentage of 83.3%, including the very good criteria. Posttest data stated that the average score of the experimental class) was 86.6 (high category). Meanwhile, the results of the N-Gain test show that the experimental class has an average N-Gain score of 0.765 (high category) and a N-Gain Percent of 76.5% (very effective). These results show that Project Based Learning is effective on students' mathematical critical thinking skills.